2000
DOI: 10.1523/jneurosci.20-24-09187.2000
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Plasticity-Related Genes in Waking and Sleep and Their Regulation by the Noradrenergic System

Abstract: Behavioral studies indicate that the ability to acquire long-term memories is severely impaired during sleep. It is unclear, however, why the highly synchronous discharge of neurons during sleep should not be followed by the induction of enduring plastic changes. Here we show that the expression of phosphorylated CRE-binding protein, Arc, and BDNF, three genes whose induction is often associated with synaptic plasticity, is high during waking and low during sleep. We also show that the induction of these genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
208
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(239 citation statements)
references
References 60 publications
24
208
1
6
Order By: Relevance
“…This is perhaps surprising because lesions of the locus coeruleus, which supplies much of the adrenergic innervation to the forebrain, cause reductions in Arc labeling (Cirelli and Tononi 2000). However, those experiments measured IEG expression following prolonged wakefulness with repeated novel object exposure, whereas our experiments examined short-term induction of Arc in response to a change in context.…”
Section: Discussion Applicability Of Arc Catfishmentioning
confidence: 91%
“…This is perhaps surprising because lesions of the locus coeruleus, which supplies much of the adrenergic innervation to the forebrain, cause reductions in Arc labeling (Cirelli and Tononi 2000). However, those experiments measured IEG expression following prolonged wakefulness with repeated novel object exposure, whereas our experiments examined short-term induction of Arc in response to a change in context.…”
Section: Discussion Applicability Of Arc Catfishmentioning
confidence: 91%
“…We found a time window during SWS ϳ2 h after the rat learned the odorreward contingency when the noradrenergic neurons of the locus ceruleus, which are usually quiescent during SWS, show a surge of activity that is never seen in animals that have not been in the learning situation (Sara et al, 2005). Learning-related delayed release of noradrenaline in forebrain neurons (Tronel et al, 2004), which are potentially engaged in reactivation during sleep, would serve as an effective signal or "molecular switch" for gene expression during a subsequent REM episode (Ribeiro et al, 1999;Cirelli and Tononi, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…There is now incontrovertible evidence that the expression of selected critical genes varies dramatically during sleep and waking events, which likely plays a major role in regulating various and long-term neuroplastic events. 176 mRNA differential display, microarray, and biochemical studies have shown that short-term sleep deprivation is associated with an immediate 1) increase in levels of pCREB (the active form of this transcription factor); 2) increase in expression of BDNF; and 3) increase in expression of BDNF's receptor, TrkB.…”
Section: Sleep Deprivationmentioning
confidence: 99%
“…In an extension of the gene expression studies, Cirelli and Tononi 176 hypothesized that a key factor responsible for the induction of the plasticity genes might be the level of activity of the neuromodulatory noradrenergic and serotonergic systems. Both of these systems project diffusely to most of the brain, where they regulate gene expression, and are only quiescent during rapid eye movement (REM) sleep.…”
Section: Sleep Deprivationmentioning
confidence: 99%